Vegetable Oils as Fuels in Diesel Engine. Engine Performance and Emissions. (December 2015) - Corsini, A.; Marchegiani, A.; Rispoli, F.; Sciulli, F.; Venturini, P.
Abstract: The EU new energy strategy represents a challenge and a boost for industries and researchers pushing them to find new solutions to supply the energy demand complying with new environmental requests. The transport sector is one of the most addicted to oil product and then pollutant. A new bio-fuels generation is being studied, but the use of the ones already available should be increased. The use of vegetable oils (VO) and waste cooking oils (WCO) could represent interesting alternative fuels for Diesel engines in some specific applications (i.e., public transportation, hybrid or marine propulsion, etc.). Moreover, VO can be produced almost everywhere in the world in relatively small plants, and WCO would represent the use of a waste material which otherwise should be disposed. However, operating a Diesel engine (DE) with a different fuel might results in some problems. Indeed VO and WCO have different characteristics compared to Diesel fuel (i.e, a smaller heating value, a larger density and viscosity), and this can affect the operation of a DE. In particular the DE is expected to have some problem at the injection system and power loss. In this work different vegetable oils (both straight and waste) are used to fuel a DE in automotive configuration and study its behavior. Tests are performed using a turbocharged, four stroke, four cylinders, water cooled, common-rail multijet DE. The influence of fuel used on engine power, specific consumption, efficiency, and exhaust opacity, are compared with those obtained fuelling with Diesel fuel.